Bearing Performance Analysis of the Thermal and Surface Roughness Effects by Finite Element Method on Slider Bearings Through Non-Newtonian Fluid-Type Lubricant - Girma Desu Tessema; Getachew Adamu Derese; Awoke Andargie Tiruneh (International Journal of Aerospace Engineering)
The finite element method was used in this study to explore the impact of surface roughness and thermal characteristics on slider bearings with non-Newtonian power-law fluid flow lubricant. One-dimensional transverse and longitudinal surface roughness models were considered under the stochastic assumption that roughness has a Gaussian random distribution. For improved computing efficiency, the surface’s uneven texture is transformed into a regular domain. For non-Newtonian power-law lubrication, a modified Reynolds equation was developed. The pressure distribution of the combined effect is less than that of the surface roughness and thermal effect in longitudinal surface roughness for all non-Newtonian parameters n and M⊛ values. As a result, there is an 1.6% reduction in load-carrying capacity performance and negligible friction force for nonparallel w=0.4 between the thermal effect and surface roughness. Nevertheless, for all non-Newtonian parameters n and M⊛ values, the pressure distribution of the thermal effect in the transverse roughness model is smaller than that of the combined and surface roughness effects. Consequently, there is an 8.9% reduction in load-carrying capacity performance and a negligible friction force for nonparallel w=0.4 between the surface roughness effect and the thermal effect condition, respectively. Additionally, the combined impacts at different temperatures were examined. As a result, in longitudinal models, the load-carrying capacity performance is better when the slider temperature is higher than the pad temperature, and vice versa for transverse models. Surface roughness and non-Newtonian power-law fluid characteristics generally enhance the performance of a slider bearing. Tables and graphs were employed to present the results.